Complex Interaction Between Low-Frequency APD Oscillations and Beat-to-Beat APD Variability in Humans Is Governed by the Sympathetic Nervous System - Duijvenboden, Stefan Van; Porter, Bradley; Pueyo, Esther; Sampedro-Puente, David Adolfo; Fernandez-Bes, Jesus; Sidhu, Baldeep; Gould, Justin; Orini, Michele; Bishop, Martin J.; Hanson, Ben; Lambiase, Pier; Razavi, Reza; et al. (Frontiers in Physiology, 2020)
Background: Recent clinical, experimental and modelling studies link oscillations of ventricular repolarization in the low frequency (LF) (approx. 0.1Hz) to arrhythmogenesis. Sympathetic provocation has been shown to enhance both LF oscillations of action potential duration (APD) and beat-to-beat variability (BVR) in humans. We hypothesised that beta-adrenergic blockade would reduce LF oscillations of APD and BVR of APD in humans and that the two processes might be linked. Methods and Results: 12 patients with normal ventricles were studied during routine electrophysiological procedures. Activation-recovery intervals (ARI) as a conventional surrogate for APD were recorded from 10 left and 10 right ventricular endocardial sites before and after acute beta-adrenergic adrenergic blockade. Cycle length was maintained constant with right ventricular pacing. Oscillatory behaviour of ARI was quantified by spectral analysis and BVR as the short-term variability. Beta-adrenergic blockade reduced LF ARI oscillations (8.6 ± 4.5 ms2 vs. 5.5 ± 3.5 ms2, p = 0.027). A significant correlation was present between the initial control values and reduction seen following beta-adrenergic blockade in LF ARI (rs = 0.62, p = 0.037) such that when initial values are high the effect is greater. A similar relationship was also seen in the beat-to beat variability of ARI (rs = 0.74, p = 0.008). There was a significant correlation between the beta-adrenergic blockade induced reduction in LF power of ARI and the witnessed reduction of beat-to-beat variability of ARI (rs = 0.74, p = 0.01). These clinical results accord with recent computational modelling studies which provide mechanistic insight into the interactions of LF oscillations and beat-to-beat variability of APD at the cellular level. Conclusions: Beta-adrenergic blockade reduces LF oscillatory behaviour of APD (ARI) in humans in vivo. Our results support the importance of LF oscillations in modulating the response of BVR to beta-adrenergic blockers, suggesting that LF oscillations may play role in modulating beta-adrenergic mechanisms underlying BVR.